The arrival of the risk paradigm to prison management in Uruguay - Vigna, Ana (Punishment in Latin America, 2025)
This chapter examines the context in which the risk model began to permeate prison management in Uruguay during the prison reform that took place from 2010 to 2020. Based on the general debate surrounding the introduction of the risk paradigm in prison policy, we focus on the particularities of importing a specific model and its associated assessment tools into a Latin American prison system. This chapter draws on interviews conducted with authorities and experts involved in the importation of this risk-based model, as well as with staff responsible for the implementation of risk assessment tools in Uruguayan prisons. The findings highlight the importance of the “intangible” aspects of prison policy, as well as the limitations of transferring programs and tools developed in the Global North to the Global South.